A unique post‐operative complication. (25th March 2015) - Modgill, O.; Mani, R.
Abstract: Aim: To highlight the importance of pre‐ and post‐operative examination of instruments used in exodontia Material and Methods: This case report concerns a fractured elevator tip following removal of a maxillary wisdom tooth, which dislodged from the socket approximately 8 weeks following the extraction. During this period, the patient remained asymptomatic. Results and Conclusions: The reported incidence of fractured instruments during operative procedures is not a common occurrence in dentistry. The vast majority of cases reported in the literature occur during endodontic treatment, and this is an accepted common risk within the endodontic speciality. However, there is very little literature regarding instrument fracture and management of cases following simple or complex exodontia. Although this is a rare incident, it reinforces the importance of checking instruments pre‐ and postsurgery by both the dental surgeon and assistants.